Mapping the Landscape of Accounting Education Quality Research: A Bibliometric Review (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study aims to map the literature on accounting education quality worldwide through bibliometric analysis. Design/Methodology/Approach: Data were obtained from the Scopus database and then bibliometrically analyzed using Bibliometrix's R package, Biblioshiny. This analysis focused on studies on accounting education quality published in the form of English articles with the query used, namely TITLE-ABS-KEY (“accounting education